2020
DOI: 10.1002/clc.23422
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular manifestations in severe and critical patients with COVID‐19

Abstract: To the editor, We would like to thank Kosuke Miki and Teruhiko Imamura for their thoughtful comments regarding our article titled "Cardiovascular Manifestations in Severe and Critical Patients with COVID-19," which was published last month in Clinical Cardiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 0 publications
0
57
1
1
Order By: Relevance
“…Chen et al 4 compared cardiovascular system variables in a small number of severely sick (39 cases) and critically sick (15 cases) COVID-19 patients, and found that diabetes, significant leukocytosis, elevated level of inflammatory elements (interleukin-6, C-reactive protein, erythrocyte sedimentation rate, D-dimer, and procalcitonin), elevated markers of myocardial injury (CK-MB, troponin-I, myoglobin, and proBNP), hypotension and tachycardia at admission, atrioventricular block, pericardial effusion, and right heart block were more prevalent in critically-ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al 4 compared cardiovascular system variables in a small number of severely sick (39 cases) and critically sick (15 cases) COVID-19 patients, and found that diabetes, significant leukocytosis, elevated level of inflammatory elements (interleukin-6, C-reactive protein, erythrocyte sedimentation rate, D-dimer, and procalcitonin), elevated markers of myocardial injury (CK-MB, troponin-I, myoglobin, and proBNP), hypotension and tachycardia at admission, atrioventricular block, pericardial effusion, and right heart block were more prevalent in critically-ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…As the pandemic of coronavirus disease 19 (COVID-19), caused by the severe acute respiratory syndrome novel coronavirus 2 (SARS-CoV-2), is evolving, an increasing number of studies are pointing to the relationship of cardiovascular disease with mortality in hospitalized patients. 1 , 2 , 3 , 4 , 5 Most previously published studies on this subject consist of small-to-large series of patients who had or developed cardiovascular events as a result of infection with SARS-CoV-2. However, few studies have compared the presence of cardiovascular disease risk factors, its manifestations, and related laboratory parameters with regard to mortality in patients with COVID-19.…”
mentioning
confidence: 99%
“…Concerns of cardiac outcomes in COVID-19 patients have been highlighted relating to worst outcomes in severely symptomatic and critically ill patients of COVID-19, with the most frequent presentation of hypotension, sinus tachycardia, arteriovenous block, ventricular tachycardia, pericardial effusion, and heart failure [ 4 ]. However, pericardial involvement is rare with the therapeutic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…However, reliable data regarding first-diagnosed AF in patients with COVID-19 are limited. Based on case reports [19] , [20] and small clinical studies [21] , [22] , [23] , [24] , new-onset AF varies between 3.6% and 6.7% in patients with COVID-19.…”
Section: Prevalence Of Af In Patients With Covid-19mentioning
confidence: 99%